Characteristics of functional ice cream produced with goat’s milk kefir in combination with mono-acylglycerol - Muhammad Fajrul Arief; Djalal Rosyidi; Lilik Eka Radiati (Universitas Sebelas Maret, 2024)
Objective: The purpose of this study was to determine the character of ice cream made from goat’s milk kefir (GMK) combined with mono-acylglycerol (MAG).Methods: GMK was produced by pasteurized goat’s milk (85oC for 15 s) and 2% kefir grain. Ice cream mix (ICM) was produced by GMK, MAG (T0= 0%, T1= 0.25%; T2= 0.50%; T3= 0.75%), 4% sucrose, and 0.1% salt. The results of observations processed using Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) if there were a significant difference between treatments.Results: Es puter (EP) made from GMK in combination with MAG has a distinctive character against T0 (control). The use of GMK decreases the pH value, thereby increasing the lactic acid and ethanol content which brings out the acidity of the product (p<0.05). In addition, increasing MAG concentration can improve the EP’s overrun to make the product more melt resistant (p<0.05). The use of GMK combined with MAG can support the viability of lactic acid bacteria (LAB) and yeast through storage in the freezer. The number of viable LAB and yeast meets WHO standards to obtained health benefit from consuming probiotic ice cream.Conclusions: To conclude, EP made from GMK in combination with 0.50% MAG was proved to be the best treatment.